Integration of Islamic Values ​​in Mathematics Learning Using Models Discovery Learning in Junior High School - Sari, Dian Rahma; Imamuddin, M.; Financhi, Wegi (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2023)
This research aims to determine the influence of Islamic nuanced learning with the Discovery Learning learning model on student learning outcomes in public schools, namely Bukittinggi 3 State Junior High School. This research uses quantitative methods with a Quasi-Experimental approach. The population in this study were all students in class VIII of Bukittinggi 3 State Junior High School which consisted of 6 classes with a total of 185 students. The research design in this study is a nonequivalent control group design which is divided into two classes, namely the experimental class and the control class. The experimental class will be treated using the Discovery Learning learning model integrated with Islamic values, while the control class will use conventional learning. The sample in this study was chosen randomly (Simple Random Sampling) from 6 classes, so class VIII-1 was chosen as the experimental class and class VIII-2 as the control class. The average N-gain score for the experimental class was 33.7% and the N-gain score for the control class was 18.1%, which shows that the N-gain score in the experimental class was higher than the control class. This shows that the experimental class using the Discovery Learning model integrated with Islamic values has a higher N-gain score than the control class using the conventional model with a lower N-gain score. So the Discovery Learning learning model integrated with Islamic values has a significant influence on student learning outcomes. Based on this research, it can be concluded that mathematics learning integrated with Islamic values not only has a positive influence on learning outcomes in Islamic schools but also has a positive influence on learning outcomes in public schools.